Comparison between digital vaginal examination and ultrasound parameters to assess fetal head station and position in labour - Pandey, Yashaswi; G. C., Apernapriya; K. S., Rajarajeshwari; S., Kalyani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The aim was to study the comparison between digital vaginal examination and ultrasound parameters to assess fetal head station and position in labour. The objective was to determine the level of agreement and to compare the findings of clinical examination with intrapartum ultrasound in the determination of fetal head station and position in labour. Methods: A prospective cohort study was done over a period of 12 months in a tertiary centre. 86 patients were followed up by digital vaginal examination and intrapartum ultrasound for determining the fetal head position and station in active labour. Categorical variables were presented in number and percentage, and continuous variables presented as mean±SD and median. Qualitative variables were correlated using Chi-square test. A p value of <0.05 was considered statistically signiﬁcant. Results: The absolute agreement between DVE and intrapartum USG for determining FHP was 43.02% in labour with a composite agreement of 66.67%. The absolute agreement between DVE and Intrapartum USG for determining fetal head station was 68.6% in labour. Accuracy of ultrasound to correctly diagnose fetal head position in labour was found to be 82.14%. Conclusions: DVE is a subjective tool which can fail to detect the correct fetal head position and station in labour in presence of certain conditions like caput succedaneum and moulding during active labour.